Uzbekistan : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The objectives of the Country Financial Accountability Assessment (CFAA) for Uzbekistan are to (i) help the government strengthen its public sector financial accountability arrangements; (ii) identify and document the most significant fiduciary risks' in the Government public financial management systems (PFM); (iii) document the existing program of reforms and capacity building to improve transparency and accountability aspects of the PFM, making additional recommendations for capacity building, if necessary. This Report has been prepared with the overriding goal of helping the government in their efforts towards strengthening control and accountability and supporting greater efficiency of public spending. The Report examines all areas of public sector accountability, including accountability and transparency aspects of the budget, accounting and external financial reporting, revenue management, the internal control environment, internal and external audit and governance of public enterprises. The goal has been to present a forward-looking analysis of current issues, focusing on practical, realistic and sequenced improvements in the Country's public financial management systems. The recommendations have taken into account the considerable capacity constraints in Uzbekistan and the limited history of reform in an environment marked by severe deficiencies in transparency and accountability.